Packet error rate analysis of OOK, DPIM and PPM modulation schemes for ground-to-satellite optical communications - Ma, Jing; Jiang, Yijun; Yu, Siyuan; Tan, Liying; Du, Wenhe (Optics communications, 2010)
Packet error rate of OOK, DPIM and PPM modulation schemes are researched for ground-to-satellite optical communication systems. Analysis process is based on threshold detection for OOK and DPIM, and optimal detection for PPM. Packet error rate of these three modulation schemes are compared for both uplink and downlink, with consideration of the turbulence introduced intensity fluctuation in the ground-to-satellite laser link. Numerical results are given, and based on it, the advantages of PPM and DPIM are discussed, with the comparison to OOK. This work can be helpful for modulation scheme selection in the ground-to-satellite laser communication system design.